Discussion of the friction of snow skis - Kunio, N.; Haizuka, S.; Tomizawa, I.; Kasahara, H.; Nakazato, H.; Saito, S.; Kaneko, K.; Ishii, A.; Abe, O. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The kinetic frictional coefficient (micro k) of skis shows a very small value and typically is explained by the meltwater lubrication theory (Bowden and Hughes). Colbeck and Warren provided experimental evidence for frictional heating by fastening a thermocouple to the bottoms of downhill and skating skis. However, even with the contributions of theory and evidence, the best thickness of the water film for sliding skis on snow and the real contact area is still unknown. We observed the micro k of short sliders at lower than -10 °C. The values at low speed and low temperature, in other words, no melt-water, show comparable values with those of Alpine skis at high speed and the best skiing temperature (-3 to -5 °C).